Quantifying the impacts of climate change and human activities on seasonal runoff in the Yongding River basin - Yong Du; Aimei Bao; Ting Zhang; Wei Ding (Ecological Indicators, 2023)
The Yongding River has ceased to flow due to the impact of human activities and climate change, inducing environmental degradation. Analyzing the driving factors is vital for environmental restoration and water resources allocation, but it is challenging especially at seasonal scale. In this paper, the monthly abcd model was constructed for the Yongding River basin and two sub-basins, namely Yanghe and Sangganhe, to quantify the relative contribution of climate change and human activities to runoff decrease. The results show that the annual runoff in the basin has been declining significantly since the 1980s, up to 30 mm/year. Human activities are the main influencing factors, with 108% contribution in the entire Yongding River basin, 122% and 98% in Yanghe and Sanggan sub-basins, respectively. The impact of human activities on runoff varies in different seasons, which is highest in the wet season, followed by irrigation season and dry season. The impact of human activities is more pronounced in July-September due to water withdrawal for irrigation and operation rules of reservoirs, which is twice as much as that in April-June. A stricter management system can alleviate the impact of human activities on runoff change.